Digital Nativity and Digital Diplomacy: Exploring Conceptual Differences Between Digital Natives and Digital Immigrants. Issue 4 (22nd May 2022) - Manor, Ilan; Kampf, Ronit
Abstract: The past decade has seen the accelerated digitalization of foreign ministries. In this study, we conceptualize digitalization as long term process in which diplomats adopt different technologies to obtain foreign policy goals. To date, only a handful of studies have investigated which factors influence digitalization. This study sought to address this gap by examining generational gaps within foreign ministries, while investigating how such gaps may prevent diplomats from obtaining communicative goals. The study thus employed the concept of digital nativity, while examining operational and conceptual gaps between digital natives and immigrants. Using a sample of 133 diplomats from six foreign ministries, the study finds there are few operational gaps between natives and immigrants. There are, however, substantial conceptual gaps between both generations. Specifically, digital immigrants use social networking sites (SNS) for one‐way message dissemination and influence and are also less likely to interact with, or value follower feedback. The same is not true of natives. Conceptual gaps may thus prevent foreign ministries from successfully marketing new policies online or gaining valuable insight that may be integrated into the policy formulation process. The study includes a series of policy recommendation that may help ministries of foreign affairs (MFAs) overcome gaps between natives and immigrants.